ANALISIS PELAKSANAAN RETRIBUSI KEBERSIHAN DI KECAMATAN TAMPAN KOTA PEKANBARU - Ravi Awlia; Sofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Analysis of the implementation of cleaning levy in Tampan subdistrict, Pekanbaru city guided by Dra. Hj.Sofia Achnes.Msi. The research to determine the execution of cleaning levy in Tampan subdistrict, Pekanbaru city. With the implementation of the cleaning levy in the Tampan subdistrict in order to improve the quality of hygiene services by paying a levy environmental hygiene in order to be more clean, organized and beautiful. The samples in this study were employees of Tampan subdistrict, head of household, head of hamlet, field officers and community with a total numbered of 55 people. The sampling technique used purposive sampling for districts employess and random sampling for neighbourhood, hamlet and field officers. Data collection is done through observation, interviews and questionnaires to the respondents. Once the data is collected then it is analyzed using quantitative descriptive analysis. Tampan subdistrict in one of the subdistricts that is authorized for the implementation of the cleaning levy. From the results of the research are still not implemented properly. Through the implementation, there was some issues of cleaning levy in the Tampan subdistrict, Pekanbaru city due to the authors select indicator that the author choose, planning, organizing, actuating dan controlling, in the category of poor judgment, it is partly also because there are many bins that have not been handled by a fleet of cleaning carriers hence, the accumulate of garbage by the edge of the road. And there are still some people that has paid their cleaning levies, where garbage is creasing every day and not all trash is transported by the janitor. While the factors that affect the implementation of cleaning levy in the Tampan subdistrict, Pekanbaru city were it’s facilities and infrastructure, area and distance landfills and landfills.Key Words : Implementation of cleaning, Tampan, Subdistrict